Enfoque gerencial en épocas de la COVID-19: sistema administrativo e innovación - Carlos Alberto Pacheco Sánchez (Mundo Fesc)
Aware of the current reality generated by the COVID-19 pandemic, managements assumed challenges with great responsibility and commitment, to achieve the permanence and continuity of their companies and, in effect, contribute to economic recovery and reactivation. Therefore, the study focuses on understanding the administrative system and the type of innovation that management adopted during the health emergency in the municipalities of Ocaña and Tibú, according to the Likert Systems, Ruiz management styles and the types of innovation established in the OSLO manual; From the methodology of a quantitative nature, the survey technique was applied to 20 active companies in the municipalities, open to the public and willing to provide information. According to the results, 80% of entrepreneurs promote product innovation and the most predominant administrative system was the autocratic-benevolent one. It is concluded that, in order to recover the economic structure and face times of change, managers must work under a collaborative approach, with a flexible and clear business structure through planning based on impacts rather than goals, and with consultative processes in response to market needs and demands.